2019
DOI: 10.3389/fimmu.2019.02743
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Dysregulation in Non-silicotic Silica Exposed Workers: A Step Toward Immune Tolerance Breakdown

Abstract: Background: Chronic silica exposure can lead to silicosis, complicated or not by autoimmune diseases (AID). The pathophysiology of silica-induced AID remains not fully understood, especially immune mechanisms that may develop in patients without yet established silicosis. We conducted a prospective clinical study to analyze the impact of crystalline silica (CS) on T cell phenotype and regulatory T cells (Tregs) frequency, as well as on auto-antibodies development in non-silicotic workers exposed to CS.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…First, the underlying silicosis lesions included predominant helper T cells with a lack of B cells, regulatory T cells, and resident memory T cells. Consistent with previous studies, 4,5 the inhalation of silica increased the activity of helper T cells, whereas it decreased the immunosuppressive function of regulatory T cells. The imbalance between helper T cells and regulatory T cells may initiate the transformation of EBVinfected B cells.…”
Section: Discussionsupporting
confidence: 92%
“…First, the underlying silicosis lesions included predominant helper T cells with a lack of B cells, regulatory T cells, and resident memory T cells. Consistent with previous studies, 4,5 the inhalation of silica increased the activity of helper T cells, whereas it decreased the immunosuppressive function of regulatory T cells. The imbalance between helper T cells and regulatory T cells may initiate the transformation of EBVinfected B cells.…”
Section: Discussionsupporting
confidence: 92%
“…The major disease-related genes of silicosis may be mapped near the HLA-B locus ( Honda et al, 1993 ). A recent study found an increased expression of the activation marker HLA-DR on CD8 + T cells of silica exposed workers ( Brilland et al, 2019 ). Similarly, our transcriptomics data showed that classic APC markers of MHC class I, especially HLA-B, were specifically increased, promoting lung inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammatory cells in moderate pain periarthritis mediate the aggregation and proliferation of fibroblasts, leading to the development of fibrosis. [ 30 ] In this study, the posterior shoulder capsule of patients with moderate pain periarthritis began to shrink, which was not significantly different from that of the unaffected side. However, the edge of the shoulder capsule was blurred, which may be related to the fibrosis of the joint capsule.…”
Section: Discussionmentioning
confidence: 57%